Analysis of MTb Rapid Molecular Test Performance Towards Microscopical Acid Fast Bacilli Examination at Labuang Baji General Hospital - Ummul Khair; Nursin Abd Kadir; Benny Rusli (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Tuberculosis (Tb) is a global health problem, which is the third leading cause of death of all infectious diseases around the world, included Indonesia. Acid Fast Bacilli (AFB) smear and rapid molecular assay for Mycobacterium tuberculosis (MTb) are the old and new examinations required for MTb laboratory diagnosis. This study aimed to compare the performance of MTb rapid molecular assay and AFB smear in diagnosis and screening for Tb patients. This observational retrospective study used a cross-sectional approach, with a purposive sampling technique of 559 patients with suspected Tb in Labuang Baji Hospital, Makassar. This study was conducted from March 2019 to June 2019 by taking data from medical records from January 2018 to December 2018 at Labuang Baji Hospital, Makassar. Three hundred and forty-nine subjects were males (62.4%), and 210 subjects were females (37.6%). This study revealed sensitivity and specificity of 98.57% and 84.96%, respectively for MTb rapid molecular assay, and 68.65% and 99.44%, respectively for AFB smear, this shows that MTb rapid molecular assay was superior to AFB smear in diagnosing TB patients.